TADABBUR AL-QUR’AN; METODE KONTEMPLASI MENJIWAI PESAN-PESAN ILAHI DALAM AL-QUR’AN - Rasyid, Aguswan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Tadabbur is one of the terms used to understand and appreciate the meaning of the verses of the Qur'an. This paper aims to analyze the meaning of tadabbur al-Qur'an, its rules, urgency, benefits, differences between tadabbur and tafsir, steps in tadabbur, and examples of tadabbur al-Qur'an. The results of the study show that tadabbur is the process of appreciating the Qur'an with the heart and mind. Its urgency is as an antidote to various diseases of the heart. Its benefits are as a door to guidance and increasing faith. The law of tadabbur is sometimes sunnah, obligatory, or makruh to abandon it. Tafsir is more focused on revealing the meaning of verses, while tadabbur is focused on reflecting on the meaning of verses to be practiced. The steps of tadabbur begin with selecting verses, reading them with tartil, repeating the recitation, delving into the meaning of the verses, and reflecting on them.Keyword: Tadabbur, al-Qur’an, tafsir